1996
DOI: 10.1002/masy.19961090114
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cells with polymers

Abstract: This paper summarizes the results of our experiments studying the effect of functional chemical groups of synthetic hydrophilic polymers on the recognition of these materials by macrophages in in vivo experiments. The interaction of keratinocytes with synthetic hydrophilic polymers in vitro is also demonstrated. The implants containing anionic groups (carboxylates) were shown to be better tolerated by nonspecific immunity. The keratinocytes are able to grow on hydrophilic polymer supports and migrate to surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Nevertheless, soft (elastic) P(HEMA‐ co ‐EDMA) I/1 (2% EDMA and NaCl as a porogen) can be recommended as a mouse ES cell support, because out of all the slabs involved in the panel study the highest number of cells colonized the hydrogel. This is in accordance with the earlier observed high growth of epidermal cells containing a pool of epidermal stem cells on the surface of neat PHEMA 34…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, soft (elastic) P(HEMA‐ co ‐EDMA) I/1 (2% EDMA and NaCl as a porogen) can be recommended as a mouse ES cell support, because out of all the slabs involved in the panel study the highest number of cells colonized the hydrogel. This is in accordance with the earlier observed high growth of epidermal cells containing a pool of epidermal stem cells on the surface of neat PHEMA 34…”
Section: Resultssupporting
confidence: 93%
“…Spreading of cells is essential for their correct attachment and early proliferation 33. In contrast, Smetana found nonstandard and altered adhesion to and spreading of fibroblasts on neat PHEMA and P(HEMA‐ co ‐methacrylic acid) materials in some cases 34. Nevertheless, soft (elastic) P(HEMA‐ co ‐EDMA) I/1 (2% EDMA and NaCl as a porogen) can be recommended as a mouse ES cell support, because out of all the slabs involved in the panel study the highest number of cells colonized the hydrogel.…”
Section: Resultsmentioning
confidence: 96%
“…This suggests that the deposition of complement protein C3bi is very low and thereby the complement system is not very active on the -COOH functionalized surface. It has also been shown that implants bearing the anionic -COOH group are well tolerated by the immune system, 76 and has resulted in reduced fibrinogen adsorption. 77 The overall negative charge of the -COOH group repels plasma protein and reduces interactions with fibrotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…some cases. 34 Nevertheless, soft (elastic) P(HEMA-co-EDMA) I/1 (2% EDMA and NaCl as a porogen) can be recommended as a mouse ES cell support, because out of all the slabs involved in the panel study the highest number of cells colonized the hydrogel. This is in accordance with the earlier observed high growth of epidermal cells containing a pool of epidermal stem cells on the surface of neat PHEMA.…”
Section: Cell Morphologymentioning
confidence: 99%
“…This is in accordance with the earlier observed high growth of epidermal cells containing a pool of epidermal stem cells on the surface of neat PHEMA. 34…”
Section: Cell Morphologymentioning
confidence: 99%